2014
DOI: 10.1111/obr.12137
|View full text |Cite
|
Sign up to set email alerts
|

Developmental coordination disorder and overweight and obesity in children: a systematic review

Abstract: Children with developmental coordination disorder (DCD) find themselves less competent than typically developing children with regard to their physical abilities and often experience failure. They are therefore likely to avoid physical activity. Physical inactivity is considered an important risk factor for developing overweight and obesity. The aim of this study is to assess the association between DCD and overweight and obesity in children and whether this association is influenced by age and/or gender. Six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 75 publications
(236 reference statements)
2
57
1
9
Order By: Relevance
“…Kindergarten-aged children with obesity are more likely to have poor gross motor skills (e.g., in locomotion and balance; Roberts, Veneri, Decker, & Gannotti, 2012). In addition, developmental coordination disorder is more likely in young children with obesity (Hendrix, Prins, & Dekkers, 2014). With children who are obese more likely to be erratic, physically clumsy, and tall for their age, young children's social cautions may be based on actual experiences of being hurt, probably unintentionally.…”
Section: Discussionmentioning
confidence: 99%
“…Kindergarten-aged children with obesity are more likely to have poor gross motor skills (e.g., in locomotion and balance; Roberts, Veneri, Decker, & Gannotti, 2012). In addition, developmental coordination disorder is more likely in young children with obesity (Hendrix, Prins, & Dekkers, 2014). With children who are obese more likely to be erratic, physically clumsy, and tall for their age, young children's social cautions may be based on actual experiences of being hurt, probably unintentionally.…”
Section: Discussionmentioning
confidence: 99%
“…8 Children with developmental coordination disorder are at increased risk of being overweight or obese. 9 In a prospective, population-based cohort study in southwestern England, probable developmental coordination disorder was identified in 346 children aged 7-9. 10 Developmental coordination disorder could be present in a child whose parents, caregiver or schoolteacher expresses concerns that he or she is unusually clumsy and is showing persistent delays in gross or fine motor milestones.…”
Section: Box 1: Evidence Used In This Reviewmentioning
confidence: 99%
“…Body mass index should be part of the general physical exam, because children with developmental coordination disorder have a propensity to be overweight or obese. 9 The American Academy of Pediatrics has outlined components of the neuromotor examination appropriate for young children. 12 Most of these are relevant for the examination of young, schoolaged children at risk of developmental coordination disorder and are summarized in Box 3.…”
Section: Clinical Examinationmentioning
confidence: 99%
“…De forma geral, os autores encontraram que crianças com TDC apresentaram três vezes mais chance de ter sobrepeso (OR: 3,44, IC 95%: 2,34-5,07) e quatro vezes mais chance de apresentar obesidade (OR: 4,00, IC 95%: 2,57-6,21) em relação àquelas sem o transtorno (CAIRNEY et al, 2010). Na Holanda, um estudo de revisão sistemática, realizado em seis bases de dados, concluiu que as crianças com TDC apresentaram maiores escores para o IMC, a circunferência da cintura e a porcentagem de gordura corporal em comparação com os escolares sem o transtorno (HENDRIX;PRINS;DEKKERS, 2014). No Canadá, outro estudo de revisão sistemática encontrou 18 manuscritos que avaliaram a composição corporal e verificaram os efeitos da mesma na proficiência motora de crianças, e 13 destes evidenciaram que a coordenação motora pobre leva a um aumento de IMC, peso corporal e percentual de gordura relativa (RIVILLIS et al, 2011).…”
Section: Variáveisunclassified
“…São também caracterizadas como "desajeitadas", por apresentarem coordenação motora pobre, problemas de ritmo, dificuldades em tarefas de esporte, lazer e interação social (GIBBS; APPLETON; APPLETON, 2007). Diante disso, pesquisas internacionais apontam que crianças com dificuldades de movimento não se engajam em situações que demandam exigências físicas e se afastam gradativamente das mesmas (HAGA, 2008;WU et al, 2010;GREEN et al, 2011), apresentando uma menor participação em atividades organizadas, como jogos com regras, o que contribui para uma baixa aptidão física, resultando em maiores riscos para o desenvolvimento de sobrepeso e obesidade (TSIOTRA et al, 2006;HANDS;LARKIN, 2006;HAGA, 2008;CAIRNEY et al, 2010;WU et al, 2010;CAIRNEY, 2011;ZHU et al, 2014;HENDRIX;PRINS;DEKKERS, 2014).…”
Section: Introductionunclassified